The Mediating Role of Creativity in the Relationship Between Organizational Leadership and Emotional Intelligence on the Performance of Equality Education Tutors - Fitri, Fitri; Rino, Rino (STKIP Singkawang, 2024)
This study aims to examine the impact of organizational leadership style and emotional intelligence on tutor performance, as well as to evaluate the mediating role of creativity in the relationship between organizational leadership style and emotional intelligence on tutor performance at Community Learning Centers (PKBM) in Padang City. This research is a quantitative study with a survey approach. The population of this study includes equality education tutors at Community Learning Centers (PKBM) in Padang City. The sample taken for this research consists of 167 equality education tutors at PKBM in Padang City. Data analysis in this study employs the SEM-PLS (Structural Equation Modeling - Partial Least Squares) method. The results of the study indicate that organizational leadership style and emotional intelligence have a positive and significant effect on the performance of educational equivalency tutors. In addition, creativity acts as a mediator in the relationship between organizational leadership style and emotional intelligence on the performance of PKBM equality education tutors in Padang City. This study contributes to the literature by expanding the understanding of organizational leadership style and emotional intelligence in influencing tutor performance. Seeing the importance of the role of creativity in providing mediating influence